Overcoming Obstacles to Broader Impacts Implementation - Alisa Zornig Gura; Gina Navoa Svarovsky; Catherine Wagner; Heather Boyd; Jessica Brookshire (The University of Alabama, 2024)
Broader Impacts (BI), or the potential for academic research to benefit society, are an important and growing function of higher education. Government agencies and private foundations increasingly expect researchers to clearly articulate BI in addition to intellectual contributions to their fields. In response to these expectations and the University of Notre Dame's (ND) mission, the Center for Broader Impacts was established in 2022 to simultaneously enhance institutional efforts to support competitive research proposal development and contribute to the overall societal impact of ND by collaborating with faculty, campus units, and external partners to design, implement, and evaluate effective BI opportunities for a wide range of audiences. Drawing from expertise across a variety of faculty and staff practitioners, as well as discussions the authors participated in with seven other diverse universities as members of the Center for Advancing Research Impact in Society's (ARIS) Program to Enhance Organizational Research Infrastructure Capacity (ORIC) Cohort 5 training sessions, this article helps inform BI practitioners in higher education of potential obstacles, opportunities, and approaches to supporting researchers across their own campuses and communities, while also highlighting nuances of working with researchers for BI partners. An example model for a sustainable approach to BI programming is also offered in the context of the future of BI.